2013
DOI: 10.1021/jp311643t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electronic and Nuclear Interactions on the Excited-State Properties and Structural Dynamics of Copper(I) Diimine Complexes

Abstract: The effects of structural constraints on the metal-to-ligand charge transfer (MLCT) excited state structural dynamics of cuprous bis-2,9-diphenyl-phenanthroline ([Cu(I)(dpp)(2)](+)) in both coordinating acetonitrile and noncoordinating toluene were studied using X-ray transient absorption (XTA) spectroscopy and density functional theory (DFT) calculations. The phenyl groups attached to the phenanthroline ligands not only effectively shield the Cu(I) center from solvent molecules, but also force a flattened tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
82
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 64 publications
10
82
0
Order By: Relevance
“…Based on the energy distinction of the shoulder feature for Cu I species at 8.986 keV, the excited state spectrum (blue curve) was obtained by subtracting 55% of the ground state from the laser-on spectrum until the shoulder feature at 8.986 keV disappears. Similar to the previous studies on Cu I diimine complexes, 17,22,25,30,31,34 the following spectral changes in the MLCT state compared to that of the ground state were observed: (1) the transition edge energy shifts to 3 eV higher, suggesting the higher positive charges in the copper center; (2) the shoulder feature at 8.986 keV, representing a 1s-to-4p z transition disappears, typically observed for pond to the Cu-C distances associated with C atoms of the phenanthroline connected directly to the four Cu-ligating N atoms as well as the C atoms of the phenyl groups in the 2,9 positions of phenanthroline. The change of these Cu-ligands can be quantified by fitting the experimental data using the IFEFFIT program.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Based on the energy distinction of the shoulder feature for Cu I species at 8.986 keV, the excited state spectrum (blue curve) was obtained by subtracting 55% of the ground state from the laser-on spectrum until the shoulder feature at 8.986 keV disappears. Similar to the previous studies on Cu I diimine complexes, 17,22,25,30,31,34 the following spectral changes in the MLCT state compared to that of the ground state were observed: (1) the transition edge energy shifts to 3 eV higher, suggesting the higher positive charges in the copper center; (2) the shoulder feature at 8.986 keV, representing a 1s-to-4p z transition disappears, typically observed for pond to the Cu-C distances associated with C atoms of the phenanthroline connected directly to the four Cu-ligating N atoms as well as the C atoms of the phenyl groups in the 2,9 positions of phenanthroline. The change of these Cu-ligands can be quantified by fitting the experimental data using the IFEFFIT program.…”
Section: Resultssupporting
confidence: 82%
“…An analogous method in the X-ray regime, X-ray transient absorption (XTA) spectroscopy, is used to track electron configurations and the corresponding molecular structural changes of [Cu I (dppS) 2 ] + by measuring the transient X-ray absorption near edge structure (XANES) and the extended X-ray absorption fine structure (EXAFS). 17,19,22,23,25,[30][31][32][33][34] We would like to answer the following questions: (1) what are the structures of the MLCT state and charge separated state structures; (2) what are the structural changes of the complex when it binds to TiO 2 nanoparticles; and (3) what we can learn from our study on Cu I diimine complex design for its applications in solar energy conversion? Understanding the molecular structures and dynamics of both photoexcited states and charge separated intermediates in the current system will not only provide guidance by revealing their practical applications in dye sensitized solar cells but also an insight into the nature of photochemical reactions.…”
mentioning
confidence: 99%
“…This results in a larger, by ∼10°, dihedral angle in the case of the latter, which is in better agreement with previous experimental observations. 92,93 Importantly, an additional gas phase geometry optimization performed within CPMD using DCACP demonstrated that the difference arises solely from the description of the π−π interactions and is not a structural change induced by the solvent shell. However, as demonstrated in Figure S6 (Supporting Information), this difference in the dihedral angle does not have a significant effect on the structure of the first solvation shell in the ground state.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Figure 4 shows an exemplary XAS spectrum as well as the two relevant regions, the so-called XANES and EXAFS region (see caption for details). XAS is a well-established approach that has been used to analyze copper complexes for almost 30 years [41] because of its high accuracy and sensitivity, which even allowed for the investigation of excited-state-structures, [42][43][44][45][46][47][48] to determine the coordination geometry of Cu-containing dendrimers, [49] metaloproteins, [50] or metastable complexes that cannot be crystallized. [19] In a recent study, it has been used to study very small structural changes upon cooling of a bulk sample of copper(I)iodide.…”
Section: Case Study (1): Cationic Mononuclear Copper Complexesmentioning
confidence: 99%